Preoperative Ratio of Neutrophils to Lymphocytes Predicts Postresection Survival in Selected Patients With Early or Intermediate Stage Hepatocellular Carcinoma. Issue 5 (February 2016) - Lu, Shi-Dong; Wang, Yan-Yan; Peng, Ning-Fu; Peng, Yu-Chong; Zhong, Jian-Hong; Qin, Hong-Gui; Xiang, Bang-De; You, Xue-Mei; Ma, Liang; Li, Le-Qun
Abstract : Abstract: This study aims to clarify the prognostic value of the preoperative neutrophil-to-lymphocyte ratio (NLR) for patients with hepatocellular carcinoma (HCC) after potentially curative hepatic resection (HR). The prognostic value of the NLR for HCC patients has not been definitely reviewed by large studies, especially for those with different Barcelona Clinic Liver Cancer (BCLC) stages. A consecutive sample of 963 HCC patients who underwent potentially curative HR was classified as having low or high NLR using a cut-off value of 2.81. Overall survival (OS) and tumor recurrence were compared for patients with low or high NLR across the total population, as well as in subgroups of patients in BCLC stages 0/A, B, or C. Clinicopathological parameters, including NLR, were evaluated to identify risk factors of OS and tumor recurrence after potentially curative hepatic resection. Multivariate analyses were performed using the Cox proportional hazards model or subdistribution hazard regression model. Multivariate analyses showed that NLR (>2.81), tumor number (>3), incomplete capsule, serum albumin (⩽35 g/L), alanine transaminase activity (>40 U/L), and macrovascular invasion were risk factors for low OS, whereas NLR (>2.81), tumor size (>5 cm), alpha fetal protein concentration (>400 ng/L), and macrovascular invasion were risk factors for low tumor recurrence. NLR > 2.81 was significantly associated with poor OS and tumor recurrence in the total patient population (both P < 0.001), as well as in the subgroups of patients in BCLC stages 0/A or B (all P < 0.05). Moreover, those with high NLR were associated with low OS ( P = 0.027), and also with slightly higher tumor recurrence than those with low NLR for the subgroups in BCLC stage B ( P = 0.058). Neither association, however, was observed among patients with BCLC stage C disease. NLR may be an independent predictor of low OS and tumor recurrence after potentially curative HR in HCC patients in BCLC stages 0/A or B.